PREVALENCE OF MISMATCH REPAIR GENE MUTATIONS IN UVEAL MELANOMA. Issue 11 (November 2020) - Toomey, Christopher B.; Protopsaltis, Nicholas J.; Phou, Samantha; Bakhoum, Mathieu F.; Thorson, John A.; Ediriwickrema, Lilangi S.; Korn, Bobby S.; Kikkawa, Don O.; Goldbaum, Michael H.; Lin, Jonathan H.
Abstract : Purpose: Uveal melanomas are associated with characteristic genetic changes. Germline mutations in mismatch repair (MMR) genes and microsatellite instability have been implicated in the development of numerous malignant neoplasms such as colon and ovarian cancers. The frequency of MMR defects in uveal melanomas has yet to be determined. Methods: Here, we analyzed the frequency of MMR gene mutations in uveal melanoma specimens from the University of California, San Diego (UCSD), The Cancer Genome Atlas (TGCA), and the Catalogue of Somatic Mutations in Cancer (COSMIC). Results: We identified only two mutations in a MMR gene: one premature stop codon in the PMS gene within the UCSD cohort (0.5% frequency) and one in-frame deletion in MSH3 within the COSMIC database (0.8% frequency). We report copy number variation of MLH1 in monosomy 3 and show decreased mRNA expression of MLH1 in uveal melanoma specimens with monosomy 3. Expression levels of MLH1 were not found to correlate with the observed number of total mutations. Conclusion: Overall, we show that mutations in MMR genes in uveal melanoma specimens are exceedingly rare, and although one copy of MLH1 is lost in monosomy 3, it does not seem to have pathologic consequences in uveal melanoma pathogenesis. Abstract : Mutations in mismatch repair genes are a rare event in uveal melanoma. Copy number variation in MLH1 occurs in association with monosomy 3 resulting in decreased mRNA expression but does not alter total mutational burden in uveal melanoma